Anti-Parkinsonian drug discovery from herbal medicines: What have we got from neurotoxic models? - Song, Ju-Xian; Sze, Stephen Cho-Wing; Ng, Tzi-Bun; Lee, Caivin Kai-Fai; Leung, George P.H.; Shaw, Pang-Chui; Tong, Yao; Zhang, Yan-Bo (Journal of ethnopharmacology, 2012)
Herbal medicines are used to treat Parkinson's disease (PD) in ancient medical systems in Asian countries such as India, China, Japan and Korea based on their own anecdotal or experience-based theories. To systematically summarize and analyze the anti-Parkinsonian activities of herbal preparations (including active compounds, herbal extracts and formulations) investigated in the neurotoxic models of PD and provide future references for basic and clinical investigations. All the herbal materials tested on in vitro and in vivo neurotoxic models of PD were retrieved from PubMed database by using pre-set searching strings. The relevant compounds and herbal extracts with anti-Parkinsonian activities were included and analyzed according to their chemical classifications or biological activities. A total of 51 herbal medicines were analyzed. A diversity of compounds isolated from herbal materials were reported to be effective on neurotoxic models of PD by modulating multiple key events or signaling pathways implicated in the pathogenesis of PD. The main structure types of these compounds belong to catechols, stilbenoids, flavonoids, phenylpropanoids and lignans, phenylethanoid glycosides and terpenes. Although some herbal extracts and formulations have shown positive results on PD animal models, the relative compounds accounting for the effects and the underlying mechanisms remain to be further investigated. Herbal medicines can be an alternative and valuable source for anti-Parkinsonian drug discovery. Compounds classified into stilbenoids, flavonoids, catechols and terpenes may be the most promising candidates for further investigation. Some well-studies compounds such as baicalein, puerarin, resveratrol, curcumin and ginsenosides deserve further consideration in clinical trials. In-depth experimental studies are still needed to evaluate the efficacy of herbal extracts and formulations in PD models.